Dancing - Colin, Noyale; Stamp, Kathryn (Emerald Publishing Limited, 2024)
The ebook edition of this title is Open Access and freely available to read online. Dance and movement are everywhere and for everyone with a body, any body. Dancing can be enjoyed in a wide range of settings without the need for additional resources or supplies. But this is not always the way that dance is perceived or experienced. Written to guide both the general public and carers and professionals in health contexts, Dancing explores the ways in which dance is being utilised to tackle health challenges, including fall prevention, depression and Parkinson's. Prioritising safe and inclusive practices, dance experts and advocates Noyale Colin and Kathryn Stamp equip readers with practical ideas for using dance and movement in developing their bodily awareness, sense of self and engagement with others, key factors in maintaining healthy identities and improving social relationships. Drawing on studies which reveal contemporary ideas about non-clinical and community-based methods for health and wellbeing through dance, Colin and Stamp offer a range of guided activities for people to undertake, information on how to get involved in dance and over a dozen case studies to inspire the exploration of dance's unique power as both a physical and a creative activity. Channelling a new application for an ancient creative practice, Dancing encourages all of us, no matter our age, circumstances or ability, to rediscover this beloved form of movement.
Includes index.
Keywords: Dance.; Dance therapy.; Medical -- Allied Health Services / Physical Therapy.; Complementary therapies, healing and health.; Physiotherapy.; Rehabilitation.; elektronické knihy; electronic books